2017
DOI: 10.1080/14767058.2017.1334047
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the fetal myocardial performance index in women with gestational impaired glucose tolerance and to assess whether this parameter is a possible prognostic indicator of adverse fetal outcome

Abstract: The MPI is impaired in fetuses in GIGT women, with fetuses with an adverse outcome having significantly higher MPI measurements compared to the fetuses with normal outcome in the GIGT group. MPI has the potential to improve fetal surveillance in gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 22 publications
3
39
1
1
Order By: Relevance
“…The same group of authors further proved the utility of mod-MPI as an excellent predictor of above-mentioned adverse perinatal outcomes, even among women with mild glucose intolerance on diet. 8 However, in our study, cardiac changes could not predict intrapartum CTG changes or low APGAR. In our study, there were no perinatal mortality, and only 2 perinatal asphyxia/acidosis.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The same group of authors further proved the utility of mod-MPI as an excellent predictor of above-mentioned adverse perinatal outcomes, even among women with mild glucose intolerance on diet. 8 However, in our study, cardiac changes could not predict intrapartum CTG changes or low APGAR. In our study, there were no perinatal mortality, and only 2 perinatal asphyxia/acidosis.…”
Section: Discussioncontrasting
confidence: 81%
“…This is in contrast to earlier studies suggesting a higher MPI thus poorer global myocardial function among foetuses of diabetic women. Such myocardial dysfunction has been demonstrated among fetuses whether diabetes is mild, 8 or severe. 9 …”
Section: Discussionmentioning
confidence: 99%
“…MPI levels are expected to change in the presence of pathological conditions that influence fetal cardiac functions. These include fetal growth restriction (FGR), twin‐twin transfusion syndrome, maternal diabetes mellitus, preeclampsia, fetal hydrops, and fetal anemia . When fetal cardiac functions influence the MPI, it may be important to decide the time of the birth.…”
Section: Introductionmentioning
confidence: 99%
“…All control births had a normal outcome. We also showed that even in milder forms of gestational diabetes there is a percentage of patients whose fetuses are sensitive to the impaired glucose tolerance and these pregnancies can behave adversely despite the clinical label of mild disease resulting in a higher than an expected rate of adverse outcome in the gestational impaired glucose tolerance (GIGT) group of 25% [8] as well as in the wellcontrolled gestational diabetic group with an adverse outcome rate of 22% [9]. Macrosomia and polyhydramnios were also noted to be associated with a signi cantly higher risk for adverse outcome in these studies [6,7,8,9].…”
Section: Resultsmentioning
confidence: 85%
“…In a series of prospective studies [6,7,8,9] we identi ed four parameters that could potentially be used in a scoring system to risk categorise gestational diabetics in terms of fetal outcome and serve as a guide to clinicians managing gestational diabetics to optimize timing of delivery. Our score is based on the myocardial performance index (MPI), E/A ratio (marker of diastolic dysfunction), increasing fetal weight (macrosomia) and increased amniotic uid index (AFI).…”
Section: Discussionmentioning
confidence: 99%